2022
DOI: 10.3389/fnut.2022.985929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of new type extrusion modification technology on supramolecular structure and in vitro glycemic release characteristics of starches with various estimated glycemic indices

Abstract: Nowadays, the highly effective modified technology to starch with various digestibility is gaining interest in food science. Here, the interactions between glycemic release characteristics and fine supramolecular structure of cassava (ECS), potato (EPS), jackfruit seed (EJFSS), maize (EMS), wheat (EWS), and rice starches (ERS) prepared with improved extrusion modification technology (IEMS) were investigated. The crystalline structures of all extruded cooking starches changed from the A-type to V-type. IEMS-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The C∞ and k of the different treatment samples were higher than those of NC. As Li et al (35) and Aaliya et al (36) reported in previous studies, the significant differences in the C∞ and k due to the partial disruption of organized chain structures by different treatment and the starch crystallization properties, which could promote the attack of the enzymes into the interiors of starch granules, resulting in C∞ and k of the various treatment samples being significantly higher than those of NC. Furthermore, this may be due to the non-catalytic combination of protein and amylase, i.e., the contact between amylase and starch is reduced, leading to a decrease in digestibility (37).…”
Section: In Vitro Digestive Kinetics Of Treatment Samplesmentioning
confidence: 83%
“…The C∞ and k of the different treatment samples were higher than those of NC. As Li et al (35) and Aaliya et al (36) reported in previous studies, the significant differences in the C∞ and k due to the partial disruption of organized chain structures by different treatment and the starch crystallization properties, which could promote the attack of the enzymes into the interiors of starch granules, resulting in C∞ and k of the various treatment samples being significantly higher than those of NC. Furthermore, this may be due to the non-catalytic combination of protein and amylase, i.e., the contact between amylase and starch is reduced, leading to a decrease in digestibility (37).…”
Section: In Vitro Digestive Kinetics Of Treatment Samplesmentioning
confidence: 83%